Pengaruh pola asuh demokratis terhadap perilaku sosial remaja - Primananda, Dwiki Septian; Marlina, Elly (Irsyad: Jurnal Bimbingan, Penyuluhan, Konseling, dan Psikoterapi Islam, 2023)
This paper aims to determine the influence of democratic parenting on adolescent social behavior among PIK-R members in Bojongloa Kaler District. The research method uses quantitative methods. Data analysis used a simple linear regression test with the sampling technique used, namely purposive sampling. The results of the hypothesis testing research showed 7,895 with a significance level of 0.009 < 0.05. So, looking at the basis for making the f test decision, namely if the significant value is 0.009, it is smaller than 0.05. This means that it is accepted, so democratic parenting has an influence on adolescent social behavior by 20.3% of the 33 research subjects. So the hypothesis in the proposed research is to accept H1. This means that there is an influence of democratic parenting on adolescent social behavior among PIK-R members in Bojongloa Kaler District.